EDUCATION AND MANPOWER IN LIBYA - اليماني د.عبد التواب (Dirasat in Economics and Business, 1970)
1.The main objective of this study is to analyze the structure of the educational system, and to discuss certain problems related to this system and their effeets on the supply of skilled labor in Libya. 2. The study has been divided into three parts. The first sims-up the crucial picture of manpower problems in the process of economic development, and presents a comparison between the output of educational institutions and manpower requirements during the period 1964-1974. The second part deals with the analysis of carrelation between education and economic development. The third and final part presents a critical assessment of the factors affecting productivity of the educational system and its impact on the supply of skilled labor in the past decade.